UJI EFEK SEDATIF FRAKSI ETANOL DAUN KRATOM (Mitragyna speciosa Korth.) PADA MENCIT JANTAN GALUR BALB/c - ., Yeni Ridayani (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2013)
Kratom (Mitragyna speciosa Korth.) is one of traditional medical plant that canproduces both stimulant effects (in low doses) and sedative effects (in high doses). Thisstudy aims to prove the sedative effect of ethanol fraction of kratom leaf, the effectivedose, and compared the effect ethanol fraction of kratom leaf with diazepam. Dry leavesof kratom was maceration in ethanol 70% for 3x24 hours. Ethanol extracts wasfractination in n-heksan, ethyl acetat, and ethanol 70% to produce fraction ethanol. Thisstudy was conducted by Traction test and Fireplace test method on male mice of BALB/cstrain. Observation as qualitative is observing the reflect act of turning the body and thecornea reflect, while quantitative is fell down time, turning the body, and turn out ofcylinder tube. Twenty five heads of mice were randomly in five groups : positive controlgroup (diazepam), negative control group (suspense CMC 1%), group of kratom leaffraction ethanol 27.20 mg/20gBW (Dose I), 54.39 mg/20gBW (Dose II), and 108.78mg/20gBW (Dose III). The results show, there are sedative effect at doses of 27.20mg/20gBW, 54.39 mg/20gBW, and 108.78 mg/20gBW, which the all dose are greaterpotential than positive control group (diazepam). Effective dose of fraction ethanol ofkratom leaf is 27.20 mg/20gBW.Keywords: sedative, kratom leaf, ethanol fraction.